Toxoplasma and reaction time: role of toxoplasmosis in the origin, preservation and geographical distribution of Rh blood group polymorphism - NOVOTNÁ, M.; HAVLÍČEK, J.; SMITH, A. P.; KOLBEKOVÁ, P.; SKALLOVÁ, A.; KLOSE, J.; GAŠOVÁ, Z.; PÍSAČKA, M.; SECHOVSKÁ, M.; FLEGR, J. (Parasitology, 2008)
The RhD protein which is the RHD gene product and a major component of the Rh blood group system carries the strongest blood group immunogen, the D-antigen. This antigen is absent in a significant minority of the human population (RhD-negatives) due to RHD deletion or alternation. The origin and persistence of this RhD polymorphism is an old evolutionary enigma. Before the advent of modern medicine, the carriers of the rarer allele (e.g. RhD-negative women in the population of RhD-positives or RhD-positive men in the population of RhD-negatives) were at a disadvantage as some of their children (RhD-positive children born to pre-immunized RhD-negative mothers) were at a higher risk of foetal or newborn death or health impairment from haemolytic disease. Therefore, the RhD-polymorphism should be unstable, unless the disadvantage of carriers of the locally less abundant allele is counterbalanced by, for example, higher viability of the heterozygotes. Here we demonstrated for the first time that among Toxoplasma-free subjects the RhD-negative men had faster reaction times than Rh-positive subjects and showed that heterozygous men with both the RhD plus and RhD minus alleles were protected against prolongation of reaction times caused by infection with the common protozoan parasite Toxoplasma gondii. Our results suggest that the balancing selection favouring heterozygotes could explain the origin and stability of the RhD polymorphism. Moreover, an unequal prevalence of toxoplasmosis in different countries could explain pronounced differences in frequencies of RhD-negative phenotype in geographically distinct populations.